Manajemen Komunikasi Organisasi di Era Digital: Tinjauan Literatur Sistematis dalam Perspektif Komunikasi Islam - Suhendri; Hafsah Juni Batubara (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Organizational communication management in the digital era faces increasing challenges due to accelerated information flows, digital communication platforms, and growing demands for transparency and accountability. This study aims to systematically review the development of organizational communication management research in the digital era and to integrate it with an Islamic communication perspective. Using a qualitative approach, this study applies a PRISMA-based systematic literature review (SLR). Literature searches were conducted through Google Scholar, Garuda, and DOAJ, yielding 312 records, which were refined to 32 articles for thematic analysis. The findings identify four main themes: the transformation of organizational communication management, internal communication and digital work practices, crisis communication and organizational reputation, and the role of Islamic communication values and ethics in organizational governance. Based on the thematic synthesis, this study proposes a conceptual model that positions Islamic communication principles as an ethical foundation for organizational communication management in the digital era. The novelty of this study lies in the explicit integration of modern organizational communication management theories with Islamic communication principles within a contextually relevant framework for organizations in Indonesia.